ANALISIS KEGAGALAN PISTON PADA KENDARAAN RODA EMPAT KAPASITAS 1000 CC - Zayadi, Ahmad (Bina Teknika, 2018)
Pistons are one of the main components of a 1000 cc engine that functions as a pressure suppressor and a recipient of pressure combustion in the combustion chamber. In the examination of the 1000 cc sedan engine that has been operating for 30,000 hours found a rough sound on the engine and experienced loss compression on the cylinder block number 2. The purpose of the study was to obtain the factors causing the deformation of the piston 1000 cc sedan vehicles. The research method used is metallographic observation using ASTM E 3 and ASTM E 112, testing hardness using ASTM E 92 and SNI 19-0409-1989 and testing chemical composition using ASTM A 751. The results of research on piston damage can be seen that observation macrostructure proves that there is plastic deformation on the surface area of the piston material, the results of microstructure observation are known to occur microcrack on the top surface of the right side of the piston, there is no change in micro hardness between the piston material in the deformed area with the deformed piston material hardness, piston material made of alloy Al-Si. In the area of the piston surface that experiences deformation, Mg2Si and Mg2Al3 compounds are formed, these compounds which cause microcrack on the piston's upper surface. Plastic deformation on the piston surface occurs due to a collision between the piston surface and the cylinder head due to the buildup of crust on the piston surface.